Factors affecting the attachment of Metallosphaera hakonensis during the colonisation of low grade mineral sulphide heaps - Bromfield, Lucinda (Centre for Bioprocess Engineering Research, 2014)
This thesis pertains to the extraction of copper via heap bioleaching, focussing specifically on the bioleaching of the mineral sulphide, chalcopyrite (CuFeS2). Industrial heap bioleaching offers an attractive alternative to conventional extraction methods, such as smelting, for processing low grade ores. There remain a number of operational challenges associated with bioleaching heaps, such as the lag time before efficient extraction is achieved and ineffective heap inoculation, as well as the difficulty in controlling the conditions within the heap.